Quantitative Analysis on the Wettability of Datura Stramonium Leaves in the Presence of Adjuvants - Shah, Pawan; Wagle, Diksha; Pokhrel, Roshna; Bhattarai, Ajaya (Journal of Nepal Chemical Society, 2025)
Datura Stramonium is an indigenous plant in Nepal but is globally cultivated for its wide medicinal applications. The knowledge of the surface properties of leaves and wettability conditions is essential for foliar applications to protect the plants. The wettability of the leaf surface is characterized by the contact angle (CA) measurement, and surface free energy (SFE) directs its wettable interactions. Three different surfactants having different charges; N-Cetyl-N, N, N-Trimethyl Ammonium Bromide (cationic), bis(2-ethylhexyl) sodium sulfosuccinate (anionic) and polyoxyethylene lauryl ether (Brij-L23) (non-ionic) and two commercial bio-wetting agents Gorkha stick more (Nepal) and Keeper (India) were utilized as adjuvants to enhance the wettability of leaves towards super-hydrophilic range (CA < 40o). The secondary parameters like molar free energy (ΔG), wetting free energy (Δg), adhesion tension (Ta), adhesion work (Wa), cohesive energy density (ec), and solubility parameter difference (Δδ) were calculated to describe the surface properties of leaves and efficiency of adjuvants in wettability. The CA value of the adaxial leaf surface was in the hydrophobic range (< 90o) while it was in the hydrophobic range on the abaxial surface (> 90o). The SFE of the adaxial leaf surface was 44.42 ± 16.52 mN m-1 whereas the abaxial surface had a SFE of 36.82 ± 1.57 mN m-1. The AOT solution showed better results among all surfactants and commercially available wetting agents by reducing CA value to the super-hydrophilic range on both adaxial and abaxial leaf surfaces below CMC. The effectiveness of adjuvants to lower the CA value follows the pattern of AOT > Gorkha stick more > CTAB > Keeper > Brij-35 solutions. The Δδ value of the abaxial leaf surface was higher than the adaxial leaf surface.